Causal Effects of PM2.5, NOx, and NO2 on Cognitive Function: A Two-sample Mendelian Randomization Study - Yilin Tang; Zhenyu Li; Yicheng Fu; Mingyi Zhao (Aerosol and Air Quality Research)
Abstract Epidemiological studies have revealed that air pollutants are related to cognitive decline, but a causal relationship has not been established. We conducted a two-sample Mendelian randomization (MR) study using pooled statistics from publicly available genome-wide association study (GWAS) data to show the association between air pollutants and cognitive decline in the European population. The exposure factors in our analysis were air pollutants, including “particulate matter air pollution (PM2.5); 2010”, “nitrogen oxides air pollution; 2010” and “nitrogen dioxide air pollution; 2010”, while our outcome variables focused on cognitive function, including the “fluid intelligence score”, “mean time to correctly identify matches”, and “number of incorrect matches in the round”. We applied various MR methods, including inverse-variance weighted (IVW), weighted median, and MR-Egger regression, to estimate the causal effects. Furthermore, we conducted heterogeneity and pleiotropy tests to ensure the robustness of our findings. Our study revealed a significant negative correlation between NOx and fluid intelligence scores (β-0.879, 95% CI [–1.423, –0.336], p = 0.002), indicating that among air pollutants, NOx has a detrimental impact on cognitive function. No significant associations were found between PM2.5 or NO2 and cognitive function. The presence of NOx is associated with a decrease in the fluid intelligence score, suggesting adverse effects of NOx on logic and reasoning skills. These findings further emphasize the importance of preventing and treating air pollution exposure and suggest that early cognitive screening in people exposed to air pollution can prevent the development of neurodegenerative diseases.